Vacum Evaporator Application in Drinking Red Ginger Instant Using Rotary Crystalizer - Siswanto; N. N. W. Triana (Future Science)
The process of evaporating red ginger extract using vacuum evaporator if the barometric condenser requires a large enough energy, to save energy, it is necessary to design a vacuum evaporator that can lower the boiling point of water and also energy-efficient by using vacuum pumps equipped condensate container. This type of vacuum pump uses a small energy when compared to using a steam jet ejector and is expected to use vacuum evaporator with this vacuum pump will be able to save electricity. Evaporator using vacuum pump with a level of vacuum reaches 0.5 atm or 360 mm Hg can lower the temperature of water evaporation to 800C so it is expected that the content in the red ginger is not much changed. The evaporation of red ginger extract to continue to become crystal used a rotary crystallizer equipped with a heater. Heating is kept at 100 ° C with a spin of 75 rpm and crystals are formed with a relatively quick 20 minutes time when compare with using stirred crystallization.